Performance of Mechanical Properties of Ultrahigh-Strength Ferrous Steels Related to Strain-Induced Transformation - Sugimoto, Koh-ichi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
A variety of topics concerning ultrahigh-strength ferrous steels were collected in this book. At present, most of the ferrous steels are applied to cold sheet parts. However, they may be used as the materials of hot-forged parts in the future, because of the excellent performance of the mechanical properties. It is hoped that many researchers will have an interest in the applications of the ferrous steels to the hot-forging parts.